Evaluating the Benefits and Risks of Genetically Modified Organisms - AL-Saeedi, Bayan Shakir Mahmood; Mahmood, Marwa Shaker; Ali, Noor Waththab (American Journal of Biology and Natural Sciences, 2025)
This paper addresses many Fields on GMOs and its uses and risk. As a result, Genetically modified organisms (GMOs) have gained significant popularity in the fast lane of modern biotechnology and anticipated to make outstanding solutions to agricultural, medical as well as scientific problems. This review deliberates the benefits and potential risks of GMO use and production. Benefits include increased crop yields, enhanced nutritional quality, resistance to pests and diseases, reduced use of chemical pesticides, and access for smallholder farmers in developing countries to valuable crops. Biomedical research, the production of bio-based industrial products and the development of medications such as vaccines all rely on GMOs. But questions persist about how they affect the environment and human health. The potential risks include unintentional gene transfer to non-target organisms, the creation of resistant weeds and pests, allergenicity, as well as undesired inhibition on natural ecosystems. There are also ethical and socio-economic concerns, such as IP issues and farmer dependence on biotech companies that make the public reluctant to adopt. This review underscores the need for thorough risk assessment, transparent legislation and continued research for balancing innovation with safety. To a certain extent, that may be true, and balance is needed to both maximize the benefits of GMOs and minimize their potential negative impacts on the environment or human health.